The pros and cons of suturing the ventral hernia defect using the intraperitoneal onlay mesh technique - Jovanović, Bojan; Rančić, Dejan; Rančić, Ljubiša; Krstović, Miljan (Vojnosanitetski pregled, 2024)
Background/Aim. Laparoscopic ventral hernia surgery, including intraperitoneal onlay mesh (IPOM), is as effective and safe as open surgery, with a lower recurrence rate. Some surgeons advocate laparoscopic primary fascial closure (PFC) with intraperitoneal mesh placement to reduce recurrence rates. The aim of this study was to compare the treatment outcome between two laparoscopic techniques: the PFC technique and mesh placement without suture closure (IPOM technique) for defects under 4 cm in patients with ventral hernias. Methods. The study sample was comprised of 50 patients who underwent laparoscopic ventral hernia surgery from January 1, 2018, until December 31, 2020. Half of the patients underwent only the IPOM technique (group of patients without the suture), while in others, this was preceded by the closure of the hernial ring (group of patients with the suture). All hernias were midline and all defects were under 4 cm. The studied groups were homogeneous according to gender and age. Comorbidities, complications, and postoperative comfort were monitored. Results. The most common (76%) hernias were primary, and the most common comorbidity was arterial hypertension (28%). One (2%) patient had intraoperative bleeding, and the most common postoperative complication was pain in 7 (14%) patients. After a three-year follow-up, there were 10 (20%) patients with complications – one hernia recurred, while 9 (18%) patients died. There was no difference in the types of occurrence of hernias, comorbidities, and intraoperative complications. The distribution of postoperative complications differed significantly (p = 0.007) between the groups. Pain was statistically significantly more prevalent in patients with sutures. During the first three months postoperatively, significantly more patients with sutures had chronic pain (χ2 = 8.140; p = 0.004). Conclusion. We recommend the application of the PFC technique in selected ventral hernia repair cases, although it can lead to more frequent postoperative pain (which, fortunately, is easily treated).